Manejo da podridão de Sclerotinia (Sclerotinia sclerotiorum) e Míldio (Bremia lactucae) na cultura de alface - Rocha, Ronicely Pereira da (2007)
Lettuce is the highest consumed vegetable in Brazil. It can however be severely affected by the fungus Sclerotinia sclerotiorum, Sclerotinia minor and Bremia lactucae; diseases considered to be ground and aerial part, respectively. The objective of this experiment was to evaluate the effect of different mulches, fungicides and one foliar fertilizer on the incidence of lettuce drop and severity of downy mildew in crisp type lettuce cultivars. Two experiments were carried out on the Fazenda Escola Capão da Onça, within the Universidade Estadual de Ponta Grossa, during the summer and winter season, with natural conditions of fungus infection. The experimental design was a completty randomized blocks with treatments arranged in split plots. This involved the combination of 3 types of mulches as black polypropylene, oats straw and bare ground. It also included two cultivars of crisp type lettuce Vera and Isabela. And four methods of control were used: 3 fungicides, metalaxyl + chlorothalonil, fenamidone and procimidone, a foliar fertilizer (Hortifós PK), and a control. For each treatment four repetitions were performed. The doses of each product applicateded were: metalaxyl + chlorothalonil 100 g a.i/100 L H2O, fenamidone 15 g a.i/100 L H2O, procimidone 75 g a.i/100 L H2O and foliar fertilizer 135 dosage of 135 g P2O5 + 100 g K2O/100 L H2O in the first application after seedling transplanting. In the subsequent applications were added 67.5 g P2O5 and 67.5 g K2O/100 L H2O and then continued until a maximum of 405 g P2O5 + 405 g K2O/100 L H2O was reached. This occurred in the fifth spraying, and this dosage remained until crop harvest. The first spray was performed at transplanting with subsequent applications occurring at intervals of 7 days. The incidence of lettuce drop was evaluated during the rosette phase and at the time of harvest, in 24 plants per parcel. The severity and the percentage of leaves with downy mildew symptoms and the plant fresh weight and biomass were evaluated in 8 plants per parcel at the time of harvest. Harvest occurred 45 and 57 days after the transplanting, for the summer and winter season experiments, respectively. For both seasons the incidence of lettuce drop was higher in the harvest phase than the phase of rosette. Covering with oat straw and black polypropylene reduced the lettuce drop in the summer season. Black polypropylene also reduced the percentage of leaves with downy mildew symptoms. The fungicide procymidone provided the best control of lettuce drop, while metalaxyl + chlorothalonil and foliar fertilizer showed better control of downy mildew. The Vera cultivar was revealed to be more susceptible to lettuce drop and downy mildew, however, it presented greater plant fresh weight and biomass than Isabela cultivar in the summer season. Keywords: ground covering, methods of control, Lactuca sativa L, Bremia lactucae and Sclerotinia sclerotiorum.